Empathy-based teaching strategies and effects within the English classroom (2023)
This paper reports a qualitative research that explored empathy-based teaching strategies in an English class at a private university in Medellín, Colombia with three students who work as coordinators and a pre-service teacher. The research asks: What effects do empathy-based teaching strategies have on students and the teacher? With a focus on a socio-critic paradigm to change both students and teachers practices inside and outside the classroom. The results of data analysis and reflection on these practices through observation and semi-structured interviews indicate an improvement in student engagement and motivation, as well as teachers' planning based on student needs. This suggests a positive development of students and teachers identities by making them more receptive to English learning and teaching.